PLANTS SENSORY-RESPONSE MECHANISMS FOR SALINITY AND HEAT STRESS - I. Rasul; H. Nadeem; M. H. Siddique; R. M. Atif; M. A. Ali; A. Umer; F. Rashid; M. Afzal; M. Abid; F. Azeem1 (Journal of Animal and Plant Sciences, 2017)
Plants, being sessile in nature, have evolved efficient sensory mechanisms to cope with the dynamic environment. Their survival depends on a network of robust and densely interconnected systems for rapid signal perception, transduction, reaction and adaptation to biotic and abiotic stimuli. Among the abiotic stresses, heat and salt stress are the major threats to modern agriculture especially in the scenario of climate change. At cellular level, signal perception and response is critical for the establishment of stress tolerance. This review gives an insight of sensory and response mechanisms induced by salt and heat stress. Saline conditions activate membrane bound sensors including ion transporters followed by activation of second messengers and signaling cascades (like TFs, MAPKs, SnRK2s and SOS pathways) for the activation of response mechanisms. Heat stress affects membrane properties and initiate sensory events followed by activation of response mechanisms (like TFs, HSFs, chaperones and osmo-protectants). Such observations emphasize the importance of signal messengers as well as transcription factors for cellular performance of plants under confrontational circumstances. Better understanding of these stress-sensory mechanisms can facilitate the breeding programs for the development of climate-resilient plants which may perform better in a challenging environment and can contribute to the global food security.
Keywords: Salinity; Heat; sensory mechanisms; stress response; climate change